Cytomegalovirus infection in renal transplant recipients diagnosed by nested-PCR - V.H. Aquino; L.T.M. Figueiredo (Brazilian Journal of Medical and Biological Research, 2001)
A prospective study of cytomegalovirus (CMV) infection was carried out on 34 renal transplant recipients managed at a General Hospital in Ribeirão Preto, SP, Brazil. Serologic tests showed that all patients were infected with CMV before renal transplantation. Two nested-PCR techniques with primers that recognize sequences of the glycoprotein B (gB) and H (gH) genes were used for CMV detection in blood and urine samples during the post-transplantation period. CMV was detected more frequently in blood samples than in urine samples (P<0.001). Thirty-three patients had CMV detected at least once in blood and/or urine samples. Seven of these patients (21.2%) were diagnosed as having symptomatic CMV infection and showed a worse clinical outcome, with a higher death rate (P = 0.03). No association between CMV viremia and graft rejection was observed. Nested-PCR was not useful to identify patients at risk for symptomatic CMV infection since only 21.2% of the patients with CMV infection were symptomatic.